If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-2 + -3z) = 13z + -13 (-2 * -4 + -3z * -4) = 13z + -13 (8 + 12z) = 13z + -13 Reorder the terms: 8 + 12z = -13 + 13z Solving 8 + 12z = -13 + 13z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-13z' to each side of the equation. 8 + 12z + -13z = -13 + 13z + -13z Combine like terms: 12z + -13z = -1z 8 + -1z = -13 + 13z + -13z Combine like terms: 13z + -13z = 0 8 + -1z = -13 + 0 8 + -1z = -13 Add '-8' to each side of the equation. 8 + -8 + -1z = -13 + -8 Combine like terms: 8 + -8 = 0 0 + -1z = -13 + -8 -1z = -13 + -8 Combine like terms: -13 + -8 = -21 -1z = -21 Divide each side by '-1'. z = 21 Simplifying z = 21
| 8+4(x-3)=4(6x+4)-4 | | 39x-46=429 | | 3(y+7)=2y+16 | | 8m-1/2+3m1/2 | | 19+133=703 | | 38+7k=32+8k | | 19+133=1116 | | 22x-123=1066 | | 143+5x=245 | | 5x+2=2x+3 | | 7x-136=16 | | -r^10+5=12 | | 3/x+5+2/2x+1=4/x-2 | | (x+6)=(4x-18) | | 10x+20=320 | | 2(3x-1)+2(4x+5)=8 | | (5x-24)=(3x-6) | | 2(2x+3)-2=5 | | 4m-18=-2m-6 | | 3x^2+7x+24=4-2x+2x^2 | | 4+2(1+x)=12 | | X+2a+3x-8=10 | | -5x+7=8x-19 | | -7(8m+16)-4=-620 | | 5/4=3/4 | | 12a^-2b^2/4a^0b^-4 | | 7x+9=-18-2x | | -3(7t+12)+11=80 | | -(5t-8)+10=-32 | | 5(3m+6)-12=123 | | -2X^3+19X^2-27X-90=0 | | -4(3m-2)=-76 |